SYNTHESIS, CHARACTERIZATION, AND OPTIMIZATION OF BIODEGRADABLE PCL-PEG-PCL TRIBLOCK COPOLIMERIC MICELLES AS NANOCARRIERS FOR HYDROPHOBIC DRUG SOLUBILITY ENHANCER - PRASETYO, JEFRI; SULAIMAN, TEUKU NANDA SAIFULLAH; LUKITANINGSIH, ENDANG (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study aims to synthesize, characterize, and optimize biodegradable polycaprolactone-polyethylene glycol-polycaprolactone (PCL-PEG-PCL) triblock copolimeric micelles as a nanocarrier for hydrophobic drug solubility enhancer of ketoprofen (K). Methods: PCL-PEG-PCL (PCEC) triblock copolymers was obtained from the synthesis of ɛ-caprolactone (ɛ-CL) and PEG by ring opening polymerization (ROP) method at different PCL: PEG ratio (2-5:1). The K-loaded PCEC triblock copolymeric micelles was obtained by solvent evaporation method. Optimization of PCEC triblock copolymers and analysis of the effect of PCL: PEG ratio factors on the responses toward particle size (PS), polydispersity index (PdI), and entrapment efficiency (EE), were carried out through the design of experiments (DoE) approach of the 22 full factorial design method using the Design-Expert software to obtain the optimum formula. Results: The higher the PCL: PEG ratio, the ZP value tends to be smaller while the PS, PdI, EE, and drug solubility may be increased, but the addition of hydrophobic blocks to some extent does not affect the EE and drug solubility. The optimum K-loaded PCEC triblock copolymeric micelles with a PCL: PEG 2.0:1 ratio has a zeta potential (ZP) of-24.07±0.35 mV, the particle size of 235.70±6.03 nm, polydispersity index of 0.30±0.06, entrapment efficiency of 87.08±0.06%, and the solubility of the K increases by 10.60 times. Conclusion: The 22full factorial design has been proven to be the suitable optimization method to determine the optimum condition that yields to the optimum results of the PS, PdI, and EE of the of the K-loaded PCEC triblock copolymer micelles.